Effect of microwave disinfection on physical and mechanical properties of acrylic resins - Consani, Rafael Leonardo Xediek; Vieira, Erica Brenoe; Mesquita, Marcelo Ferraz; Mendes, Wilson Batista; Arioli-Filho, João Neudenir [UNESP] (FapUNIFESP (SciELO), 2008)
This study evaluated the effect of microwave energy on the hardness, impact strength and flexural strength of the Clássico, Onda-Cryl and QC-20 acrylic resins. Aluminum die were embedded in metallic or plastic flasks with type III dental stone, in accordance with the traditional packing technique. A mixing powder/liquid ratio was used according to the manufacturer's instructions. After polymerization in water batch at 74°C for 9 h, boiling water for 20 min or microwave energy at 900 W for 10 min, the specimens were deflasked after flask cooling at room temperature, and submitted to finishing. Specimens non-disinfected and disinfected by microwave irradiation were submitted to hardness, impact and flexural strength tests. Each specimen was immersed in distilled water and disinfected in a microwave oven calibrated to 650 W for 3 min. Knoop hardness test was performed with 25 g load for 10 s, impact test was carried out using the Charpy system with 40 kpcm, and 3-point bending test with a crosshead speed of 0.5 mm/min until fracture. Data were submitted to statistical analysis by ANOVA and Tukey's test (α=0.05). Disinfection by microwave energy decreased the hardness of Clássico and Onda-Cryl acrylic resins, but no effect was observed on the impact and flexural strength of all tested resins.
Keywords: Acrylic resin; Flexural strength; Hardness; Impact; Microwave disinfection; acrylic acid resin; dental care; disinfection; equipment; hardness; materials testing; methodology; microwave radiation; pliability; radiation exposure; Acrylic Resins; Dental Stress Analysis; Disinfection; Equipment Contamination; Materials Testing; Microwaves; Pliability